The influence of tooth brushing time over saliva buffering capacity - Mulyanti, Sri; Anggrawati, Hetty (Padjadjaran Journal of Dentistry, 2014)
Saliva gives a considerable influence against the growth of dental caries as a natural defense against caries. the things very important about saliva are its flow rate and buffering capacity. the decrease in saliva flow rate might cause food retention that furthermore would turn into dental plaques, meanwhile itâs buffering capacity will play a considerable role in maintaining the salivaâs pH and remineralization process of the teeth. One of the mechanisms which are considered to be effective in preventing dental caries is teeth brushing which could change the pH of 5,6 to a normal level. And the right time of teeth brushing will provide an optimal result.The study aims to reveal the influence of teeth brushing time against saliva buffering capacity. The study is an analytic study using a quasi-experimental design. The samples of the study are 20 (twenty) students of dentistry in Health Ministry of Bandung which was purposively selected the sample is divided into 3 groups. The first group is treated by brushing their teeth right after eating bread, the second and third group is treated 15 and 30 minutes after eating bread. The hypothesis uses Kruskal Wallis hypothesis continued by Mann Whitney test, strikethrough. The study reveals that the group brushed their teeth right after eating bread shows low category of saliva buffering is that 55% meanwhile those who brushed their teeth 15 and 30 minutes after eating bread exhibits the result as much as 65% and 25 % Thus the last group is included to those who have a medium risk of suffering from dental carries. The statistics of Kruskal Wallis test within the confidence level of 95% shows that there is an influence of teeth brushing time over the saliva buffering capacity with p<0,001. Mann Whitney test shows that the time of teeth brushing within 15 minutes after eating is better than the group who brush their teeth 30 minutes after eating.